Differential pulmonary effects of CoO and La2O3 metal oxide nanoparticle responses during aerosolized inhalation in mice. Issue 1 (December 2015) - Sisler, Jennifer; Li, Ruibin; McKinney, Walter; Mercer, Robert; Ji, Zhaoxia; Xia, Tian; Wang, Xiang; Shaffer, Justine; Orandle, Marlene; Mihalchik, Amy; Battelli, Lori; Chen, Bean; et al.
Abstract Background Although classified as metal oxides, cobalt monoxide (CoO) and lanthanum oxide (La2 O3 ) nanoparticles, as representative transition and rare earth oxides, exhibit distinct material properties that may result in different hazardous potential in the lung. The current study was undertaken to compare the pulmonary effects of aerosolized whole body inhalation of these nanoparticles in mice. Results Mice were exposed to filtered air (control) and 10 or 30 mg/m3 of each particle type for 4 days and then examined at 1 h, 1, 7 and 56 days post-exposure. The whole lung burden 1 h after the 4 day inhalation of CoO nanoparticles was 25 % of that for La2 O3 nanoparticles. At 56 days post exposure, < 1 % of CoO nanoparticles remained in the lungs; however, 22–50 % of the La2 O3 nanoparticles lung burden 1 h post exposure was retained at 56 days post exposure for low and high exposures. Significant accumulation of La2 O3 nanoparticles in the tracheobronchial lymph nodes was noted at 56 days post exposure. When exposed to phagolysosomal simulated fluid, La nanoparticles formed urchin-shaped LaPO4 structures, suggesting that retention of this rare earth oxide nanoparticle may be due to complexation of cellular phosphates within lysosomes. CoO nanoparticles caused greater lactate dehydrogenase release in the bronchoalveolar fluid (BALF) compared to La2 O3 nanoparticles at 1 day post exposure, while BAL cell differentials indicate that La2 O3 nanoparticles generated more inflammatory cell infiltration at all doses and exposure points. Histopathological analysis showed acute inflammatory changes at 1 day after inhalation of either CoO or La2 O3 nanoparticles. Only the 30 mg/m3 La2 O3 nanoparticles exposure caused chronic inflammatory changes and minimal fibrosis at day 56 post exposure. This is in agreement with activation of the NRLP3 inflammasome after in vitro exposure of differentiated THP-1 macrophages to La2 O3 but not after CoO nanoparticles exposure. Conclusion Taken together, the inhalation studies confirmed the trend of our previous sub-acute aspiration study, which reported that CoO nanoparticles induced more acute pulmonary toxicity, while La2 O3 nanoparticles caused chronic inflammatory changes and minimal fibrosis.